Rapid Introgression of the Fusarium Wilt Resistance Gene into an Elite Cabbage Line through the Combined Application of a Microspore Culture, Genome Background Analysis, and Disease Resistance-Specific Marker Assisted Foreground Selection - Liu, Xing; Han, Fengqing; Kong, Congcong; Fang, Zhiyuan; Yang, Limei; Zhang, Yangyong; Zhuang, Mu; Liu, Yumei; Li, Zhansheng; Lv, Honghao (Frontiers in Plant Science, 2017)
Cabbage is an economically important vegetable worldwide. Cabbage Fusarium Wilt (CFW) is a destructive disease that results in considerable yield and quality losses in cole crops. The use of CFW-resistant varieties is the most effective strategy to mitigate the effects of CFW. 01-20 is an elite cabbage line with desirable traits and a high combining ability, but it is highly susceptible to CFW. To rapidly transfer a CFW resistance gene into 01-20 plants, we used microspore cultures to develop 230 doubled haploid (DH) lines from a cross between 01-20 (highly susceptible) and 96-100 (highly resistant). One of the generated DH lines (i.e., D134) was highly resistant to CFW and exhibited a phenotypic performance that was similar to that of line 01-20. Therefore, D134 was applied as the resistance donor parent. We generated 24 insertion–deletion markers using whole genome resequencing data for lines 01-20 and 96-100 to analyze the genomic backgrounds of backcross (BC) progenies. Based on the CFW resistance gene FOC1, a simple sequence repeat marker (i.e., Frg13) was developed for foreground selections. We screened 240 BC1 individuals and 280 BC2 individuals with these markers and assessed their phenotypic performance. The proportion of recurrent parent genome (PRPG) of the best individuals in BC1 and BC2 were 95.8% and 99.1%. Finally, a best individual designated as YR01-20 was identified from 80 BC2F1 individuals, with homozygous FOC1 allele and genomic background and phenotype almost the same as those of 01-20. Our results may provide a rapid and efficient way of improving elite lines through the combined application of microspore culture, whole-genome background analysis and disease resistance-specific marker selection. Additionally, the cabbage lines developed in this study represent elite materials useful for the breeding of new CFW-resistant cabbage varieties.